Code Switching in Ahmed Yerima's Akudaaya: A Sociolinguistic Study - Aderinsola , Adebusayo Shodunke (Corpus Intellectual, 2025)
This paper aims to explore the phenomenon of code- switching in Ahmed Yerima's play Akudaaya from a sociolinguistic perspective, utilising the theoretical framework proposed by Poplack in her 1980 theory of code-switching. The study investigates the linguistic motivations and sociocultural factors that influence code switching patterns in the play, shedding light on how language choice serves as a tool for character development and thematic representation. By analysing instances of inter-sentential code-switching, intra-sentential code-switching, and tag- switching within the context of the play, this study contributes to a deeper understanding of the complex interplay between language, identity, and sociocultural dynamics.